Evolutionary insights and expression dynamics of the CaNFYB transcription factor gene family in pepper (Capsicum annuum) under salinity stress - Abd El Moneim, Diaa; Mansour, Hassan; Alshegaihi, Rana M.; Safhi, Fatmah Ahmed; Alwutayd, Khairiah Mubarak; Alshamrani, Rahma; Alamri, Amnah; Felembam, Wessam; Abuzaid, Amani Omar; Magdy, Mahmoud (Frontiers in Genetics, 2023)
The Capsicum annuum nuclear factor Y subunit B (CaNFYB) gene family plays a significant role in diverse biological processes, including plant responses to abiotic stressors such as salinity. In this study, we provide a comprehensive analysis of the CaNFYB gene family in pepper, encompassing their identification, structural details, evolutionary relationships, regulatory elements in promoter regions, and expression profiles under salinity stress. A total of 19 CaNFYB genes were identified and subsequently characterized based on their secondary protein structures, revealing conserved domains essential for their functionality. Chromosomal distribution showed a non-random localization of these genes, suggesting potential clusters or hotspots for NFYB genes on specific chromosomes. The evolutionary analysis focused on pepper and comparison with other plant species indicated a complex tapestry of relationships with distinct evolutionary events, including gene duplication. Moreover, promoter cis-element analysis highlighted potential regulatory intricacies, with notable occurrences of light-responsive and stress-responsive binding sites. In response to salinity stress, several CaNFYB genes demonstrated significant temporal expression variations, particularly in the roots, elucidating their role in stress adaptation. Particularly CaNFYB01, CaNFYB18, and CaNFYB19, play a pivotal role in early salinity stress response, potentially through specific regulatory mechanisms elucidated by their cis-elements. Their evolutionary clustering with other Solanaceae family members suggests conserved ancestral functions vital for the family’s survival under stress. This study provides foundational knowledge on the CaNFYB gene family in C. annuum, paving the way for further research to understand their functional implications in pepper plants and relative species and their potential utilization in breeding programs to enhance salinity tolerance.